Modificaciones producidas por la edad en el flujo transmitral en el perro - Casalonga, O. (2012)
The authors studied the effects of age on transmitral flow by means of pulse wave Doppler in 96 cardiologically healthy dogs separated into five age groups (group 1, 1 to 3 years [n=11]; group 2, 4 to 6 years [n=22]; group 3, 7 to 9 years [n=33]; group 4, 10 a 12 years [n=15]; group 5, over 13 years [n=16]). The results indicate that age significantly influence the transmitral flow characteristics. Individuals under 6 years of age showed normal transmitral flow while older animals showed the greatest alterations. The E wave peak velocity was significantly different (p<0.0001) between the last three groups (3, 4 and 5) and the first two groups (1 and 2). The same was true for the deceleration slope of E-wave (p<0.0001) and A wave peak velocity (p<0.0003). Regarding the E/A ratio significant differences were found between groups 1 and 2, group3 (p<0.0001) and the two last groups (4 and 5; p<0.0001). There were no significant differences (p>0.05) among the five groups for the parameters\nDeceleration time of E wave and the Isovolumic relaxation time.